Skeletal muscle proteome analysis underpins multifaceted mitochondrial dysfunction in Friedreich’s ataxia - Indelicato, Elisabetta; Faserl, Klaus; Amprosi, Matthias; Nachbauer, Wolfgang; Schneider, Rainer; Wanschitz, Julia; Sarg, Bettina; Boesch, Sylvia (Frontiers in Neuroscience, 2023)
Friedreich´s Ataxia (FRDA) is a severe multisystemic disorder caused by a deficiency of the mitochondrial protein frataxin. While some aspects of FRDA pathology are developmental, the causes underlying the steady progression are unclear. The inaccessibility of key affected tissues to sampling is a main hurdle. Skeletal muscle displays a disease phenotype and may be sampled in vivo to address open questions on FRDA pathophysiology. Thus, we performed a quantitative mass spectrometrybased proteomics analysis in gastrocnemius skeletal muscle biopsies from genetically confirmed FRDA patients (n=5) and controls. Obtained data files were processed using Proteome Discoverer and searched by Sequest HT engine against a Uniprot human reference proteome database. Comparing skeletal muscle proteomics profiles between FRDA and controls, we identified 228 significant DE proteins, of which 227 were downregulated in FRDA. Principal component analysis showed a clear separation between FRDA and control samples. Interactome analysis revealed clustering of DE proteins in oxidative phosphorylation, ribosomal elements, mitochondrial architecture control and fission/fusion pathways. DE findings in the muscle-specific proteomics suggested a shift towards fasttwitching glycolytic fibers. Notably, most DE proteins (169/228, 74%) are target of the transcription factor nuclear factor-erythroid 2.Our data corroborate a mitochondrial biosignature of FRDA, which extends beyond a mere oxidative phosphorylation failure. Skeletal muscle proteomics highlighted a derangement of mitochondrial architecture and maintenance pathways and a likely adaptive metabolic shift of contractile proteins.The present findings are relevant for the design of future therapeutic strategies and highlight the value of skeletal muscle -omics as disease state readout in FRDA.